Changes in Coronal Alignment of the Knee Joint after Supramalleolar Osteotomy - Chun, Dong-Il; Kim, Jahyung; Won, Sung Hun; Cho, Jaeho; Ha, Jeongku; Kil, Minkyu; Yi, Young (BioMed research international, 2021)
Background. Assessing knee joint orientation changes after SMO may help clinical advancement in managing patients with ipsilateral ankle and knee joint arthritis. However, knee joint changes after supramalleolar osteotomy (SMO) have not been reported. We investigated changes in coronal alignment of the knee joint after SMO. Methods. In this multicentre study, from January 2014 to December 2018, 47 ankles with varus osteoarthritis treated with SMO were retrospectively identified. Ankle joint changes were assessed using the tibiotalar angle, talar tilt angle, and lateral distal tibial angle (LDTA); knee joint changes using the medial proximal tibial angle (MPTA), medial and lateral joint space widths (mJSW and lJSW, respectively), and medial and lateral joint line convergence angles (JLCA); and lower limb alignment changes using mechanical axis deviation angle (MADA) and the hip-knee-ankle (HKA) angle measured on full-length anteroposterior radiographs of the lower extremity. Correlation analysis and binary logistic regression analysis were performed. Results. Postoperatively, LDTA (p<0.001) and tibiotalar angle (p<0.001) significantly changed, indicating meaningful improvement in the ankle joint varus deformity. Regarding the knee joint changes, JLCA significantly changed into valgus direction (p=0.044). As for lower limb alignment changes, MADA significantly decreased (p<0.001), whereas the HKA angle significantly increased (p<0.001). In univariate and multivariate logistic regression analyses, changes in the MADA (p<0.001) and the HKA angle (p<0.001) were significantly correlated with the correction angle. Conclusions. SMO remarkably improves ankle joint varus deformity, followed by significant lower limb alignment changes. Despite meaningful changes in JLCA, the relationship between the amount of osteotomy near the ankle joint and improvement in knee joint radiographic parameters was not significant. Radiographic parameters of the knee joint would less likely be changed following SMO.